CORRECTION OF THE DEVIATED SEPTUM: FROM THE ENDOSCOPIC ERA (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Obstructed nasal breathing can occur due to deviation of the nasal septum. When the external nose appears grossly normal and cosmesis is not the focus, septoplasty has been the procedure used to straighten the septum with the goal of improving nasal airflow. Septoplasty has evolved over time.